Forecasting Vertebrate Species Habitat Suitability and Ecoregion Types under Future Climate Change Scenarios Using Species Distribution Modeling (SDM) - Veneros Guevara, Jaris Emmanuel (2023)
Climate change is a global concern, and its impact on environmental variables such as temperature and annual precipitation is spatially unknown in the Desert, Andean and Jungle Ecoregions for Peru, Ecuador and Colombia. In this study we perform a general review of climate drivers for South America and explore climate data using the GCM package compareR. Our results showed that all global circulation models demonstrated temperature increases for Peru, Ecuador and Colombia. On the other hand, most GCMs showed increases in rainfall. We performed non-parametric tests (Kruskal-Wallis Test) to evaluate whether the median temperatures and precipitation in the Sechura Desert, Páramo and Napo Tropical Forest ecoregions are the same for the baseline and climate change scenarios. We reject the null hypothesis that the medians are equal for both temperature and precipitation at baseline vs 2050 RCPs (2.6, 4.5, and 5.8). A spatial analysis was performed to visualize temperature and precipitation variations between the RCPs versus the baseline, and spatial variation can be observed at the country or ecoregion level. In conclusion, climate change is likely to have a significant impact on the environmental variables of temperature and precipitation in South American ecoregions. Our study provides important data on the potential impacts of climate change on these important ecosystems.